PENGEMBANGAN SISTEM APLIKASI LOKASI RUMAH KOST KABUPATEN PRINGSEWU BERBASIS WEB MOBILE - Elisabet Yunaeti Anggareni; Elieser Rudi HCN; Mad Muhaidi (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2018)
Boarding house today is a promising business, this is because more and more people need a place to live. But in determining the location of boarding house is very difficult so that the need for an application system to solve the problem. This is what makes the author wants to design an application system location of boarding house Pringsewu District. Number of choice of location of boarding house in Pritsewu District then made an application that serves to determine the location of the right board for easier and faster. This system is a system that can help the community in determining the location of the boarding house as desired. With this application is expected to help the community in finding the location of suitable boarding house, especially in Pringsewu District. The method used in making this application is the method of observation.